2014
DOI: 10.1080/10255842.2014.881806
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of fluid–structure interaction in bypassed DeBakey III aortic dissection

Abstract: It was found that bypass graft alone could achieve great effects in treating aortic dissection. In order to investigate the mechanical mechanism and the haemodynamic validity of the bypassing treatment for DeBakey III aortic dissection, patient-specific models of DeBakey III aortic dissection treated with different bypassing strategies were constructed. One of the bypassing strategies is bypassing between ascending aorta and abdominal aorta, and the other is bypassing between left subclavian artery and abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…It is not clear at present why such a discrepancy exists between these data and the aforementioned imaging studies. In an FSI simulation of a simplified dissected aorta, Qiao et al [ 15 ], found flap displacements of only up to 0.15 mm , which may be attributable to the use of a Young’s modulus of 100 MPa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear at present why such a discrepancy exists between these data and the aforementioned imaging studies. In an FSI simulation of a simplified dissected aorta, Qiao et al [ 15 ], found flap displacements of only up to 0.15 mm , which may be attributable to the use of a Young’s modulus of 100 MPa .…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, patient-tailored computational-fluid dynamics (CFD) approaches, wherein imaging data is used to construct a model of the patient’s aorta in which the flow is simulated, can provide data on WSS and pressure with high resolution [ 8 - 11 ]. Furthermore, the models once validated can be easily altered to evaluate the efficacy of various virtual intervention approaches [ 12 - 15 ]. However, as with most numerical simulations, these approaches require a number of assumptions to be made regarding the boundary conditions (pressure or flow, dynamic or static) and flow properties (viscosity model for blood, turbulence).…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant flow patterns result in large spatial variations in wall shear stress (WSS), with high values near the tears and low shear stress in the proximal section of the FL [11]. Computational models have also been developed to predict FL thrombosis and the effectiveness of endovascular and surgical treatments [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FSI models are difficult to setup and demand significant computational effort to be resolved. ADs are arguably one of the most challenging aortic pathologies to simulate and hence it is not surprising that there are only a handful of studies on AD accounting for wall motion in the literature [12,14,15]. Chen et al [16] recently presented an FSI model of an idealised dissected porcine aorta without re-entry tear, assuming a homogeneous linear-elastic material model.…”
Section: Introductionmentioning
confidence: 99%